Phase 1 of the 2005 Commencement ceremony and the drama department's Phase 2 ceremony in Goddard Chapel. Photo 0279 - Martin, Winslow (Tufts Archival Research Center, 2008)
Phase 1 of the 2005 Commencement ceremony and the drama department's Phase 2 ceremony in Goddard Chapel.